2019
DOI: 10.1158/1541-7786.mcr-19-0434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Characterization of Growth Hormone–Secreting Pituitary Tumors

Abstract: Somatic driver mechanisms of pituitary adenoma pathogenesis have remained incompletely characterized; apart from mutations in the stimulatory Ga protein (Ga s encoded by GNAS) causing activated cAMP synthesis, pathogenic variants are rarely found in growth hormone-secreting pituitary tumors (somatotropinomas). The purpose of the current work was to clarify how genetic and epigenetic alterations contribute to the development of somatotropinomas by conducting an integrated copy number alteration, whole-genome an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
18
1
Order By: Relevance
“…Contrary to Hage et al and Valimaki et al, we did not find a significant association between GNAS mutations (found in 13/53 tumors) and the quantity of genomic alterations in somatotroph tumors [9,33]. We identified 13 GNASwt tumors presenting gains of the 20q region, these tumors further presenting a high quantity of alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to Hage et al and Valimaki et al, we did not find a significant association between GNAS mutations (found in 13/53 tumors) and the quantity of genomic alterations in somatotroph tumors [9,33]. We identified 13 GNASwt tumors presenting gains of the 20q region, these tumors further presenting a high quantity of alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…Dopamine receptor 2 expression is increased in GNAS -mutated tumors, potentially allowing for GNAS mutation status in predicting the response to dopamine agonists in GH-PTs ( 17 ). Recently, DNA methylation-activated inhibitory Gα (Gαi) -signaling was found in GNAS -mutation-positive GH-PTs ( 152 ). Patients with somatic mosaicism for codon 201 GNAS develop McCune-Albright syndrome, characterized by somato- or somatomammotroph hyperplasia or tumor, polyostotic fibrous dysplasia, cafe-au-lait spots, and precocious puberty ( 153 ).…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…GH-PTs show greater genomic disruption than ACTH-PTs as well as inactive tumors with no clinical evidence of hormone secretion ( 120 ). Subgroups of GNAS -mutation negative GH-secreting tumors show high levels of genomic instability ( 152 ) with 20 q amplification ( GNAS locus) ( 17 , 143 , 181 ), which may be an alternative mechanism of increased signaling through GNAS driving somatotroph tumorigenesis. GH-PTs with recurrent aneuploidy showed high expression of pituitary tumor transforming gene 1 (PTTG1), which is a regulator of sister chromatid segregation, this may subsequently drive chromosomal instability ( 152 , 182 , 183 ).…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Among pituitary tumors, the growth hormone (GH)-secreting ones (somatotropinomas) account for about 15%-20% of cases, causing gigantism in children/adolescents while in adults leads to the clinical picture of acromegaly characterized by overgrowth of bone and cartilages, and cardiovascular, metabolic, respiratory and neoplastic complications (1)(2)(3). Somatotropinoma tumorigenesis and pathophysiology is only partially understood, although several efforts have been made to identify underlying genetic and epigenetic abnormalities (4).…”
Section: Introductionmentioning
confidence: 99%
“…Somatotropinoma tumorigenesis and pathophysiology is only partially understood, although several efforts have been made to identify underlying genetic and epigenetic abnormalities (4). In terms of genetic background, the most frequently somatic pathogenic events in somatotropinomas (around 35% of cases) are gain-of-function mutations in the stimulatory guanine nucleotide (GTP) binding protein alpha (Gas) encoded by the GNAS gene, with consequent constitutive cAMP pathway activation (3,5). On the other hand, next generation sequencing approach has revealed few relevant somatic alterations in these tumors such as USP8, GNAS, USP48, and BRAF (5).…”
Section: Introductionmentioning
confidence: 99%